PENGARUH PENAMBAHAN SERAT KAYU PINUS DAN BAMBU PETUNG TERHADAP KUALITAS PAPAN SERAT KERAPATAN SEDANG KAYU MAHANG DENGAN PEREKAT ASAM MALAT - Agus Wahyudi; T.A. Prayitno; Ragil Widyorini; J.P. Gentur Sutapa (Jurnal Penelitian Hasil Hutan, 2019)
Properties and quality of fibreboard products are much influenced by quality of the fiber materials, pressing process, and the amount and type of the used adhesive. The use of malic acid adhesives in the manufacture of medium density fibreboards (MDF) from mahang wood has low mechanical properties, especially modulus of static value. This paper studies on the effect of adding long fibers of pine wood and petung bamboo to improve the properties of MDF mahang wood with malic acid adhesives. The compositions ratio of mahang wood, pine wood, and petung bamboo fiber are 100/0/0, 90/10/0, 80/20/0, 90/0/10, 80/0/20, and 80/10/0, malic acid content of 25 wt % based on dry weight fibers and hot pressing at 180ºC for 10 minutes. Physical and mechanical tests were accomplished according to JIS 5905-2003 testing standard. Result shows the addition of long fibers of pine wood and petung bamboo increased the mechanical value of MDF from mahang wood. The best mixture of fiber is 90% mahang wood fiber and 10% petung bamboo, with value internal bonding 0.7 MPa, modulus of rupture 9.11 Mpa, and modulus of elasticity 2.5 GPa.